New knowledge about grinding using MQL simultaneous to cooled air and MQL combined to wheel cleaning jet technique - Ribeiro, Fernando Sabino Fonteque [UNESP] (2020)
The final quality of mechanical components has been increasingly desired in the industry. This final quality is directly linked to surface roughness, geometric deviations, and mechanical integrity of components subjected to machining processes. For that, the industry makes use of cutting fluids so that it is possible to achieve such conditions. In the case of grinding, the application of cutting fluid in abundance allows a great reduction in temperature, as well as a better removal of chips from the cutting surface of the wheel. However, the problems generated by the cutting fluid related to environmental and labor liabilities have increasingly led to the development of effective techniques for grinding with minimal amounts of cutting fluid. The difficulties linked to the use of MQL are concentrated in the low rate of heat removal and in the clogging of the cutting surface, varying according to the type of grinding wheel applied. In this sense, the present work proposes comparison during the cylindrical grinding of hardened steel under conventional lubrication conditions, minimum quantity lubricant (MQL), cooled air MQL (MQL + CA), and MQL with wheel cleaning jet (MQL + WCJ), using aluminum oxide (Al2O3) and CBN grinding wheels. The results are presented in terms of surface roughness, roundness error, microhardness, tangential force, diametrical wear of the grinding wheels, and G-ratio. The application of MQL + CA and MQL + WCJ can improve the use of MQL. In terms of roughness, the MQL + WCJ presents values close to the conventional increase of 8.8%. Roundness errors were reduced by up to 36.3% during the application of MQL + CA and MQL + WCJ and up to 10.5% for the tangential force. Thus, these advanced techniques have shown that the conditions are feasible for the application of pure MQL towards an eco-friendly grinding process.